Dimensions of Transformational Leadership Headmaster - Effendi, Mukhlison; Maunah, Binti (Cendekia: Jurnal Kependidikan dan Kemasyarakatan, 2021)
Leadership has a decisive position in the organization. Leaders who carry out their leadership effectively can lead others to achieve the goals; on the contrary, leaders as figures have no influence. Their leadership promotes weak organizational performance, which turns it into a downturn. This study aims to examine the dimensions of the principal’s transformational leadership and its urgency for reform. By employing the literature study method, this study depicted that to run the principal’s transformational leadership smoothly; they must apply all dimensions of idealized influence, inspirational motivation, intellectual stimulation, and individual consideration. Suppose the principal can apply the 4I dimensions of transformational leadership. In that case, as a leader of educational institutions, the principal succeeds in bringing changes to educational organizations for the better. Kepemimpinan memiliki kedudukan yang menentukan dalam organisasi. Pemimpin yang melaksanakan kepemimpinannya secara efektif dapat menggerakkan orang/personel ke arah tujuan yang dicita-citakan, sebaliknya pemimpin yang keberadaannya hanya sebagai figur, tidak memiliki pengaruh, kepemimpinannya dapat mengakibatkan lemahnya kinerja organisasi, yang pada akhirnya dapat menciptakan keterpurukan. Penelitian ini bertujuan untuk menelaah dimensi kepemimpinan transformasional kepala sekolah dan urgensinya terhadap pembaharuan. Dengan metode studi pustaka dapat dipaparkan bahwa agar kepemimpinan kepala sekolah dapat berjalan lancar, kepala sekolah harus mampu menerapkan seluruh dimensi idealiced influence, inspirational motivation, intellectual stimulation dan individual consideration. Apabila kepala sekolah mampu menerapkan dimensi 4I kepemimpinan transformasional tersebut, maka kepala sekolah sebagai pemimpin lembaga pendidikan akan berhasil membawa perubahan pada organisasi pendidikan ke arah lebih baik.